2019
DOI: 10.1097/rlu.0000000000002348
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting Response to Neoadjuvant Chemotherapy in Patients With Breast Cancer

Abstract: Purpose The aim of this study was to develop a combined statistical model using both clinicopathological factors and texture parameters from 18F-FDG PET/CT to predict responses to neoadjuvant chemotherapy in patients with breast cancer. Materials and Methods A total of 435 patients with breast cancer were retrospectively enrolled. Clinical and pathological data were obtained from electronic medical records. Texture parameters were extracted from pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…Radiomics analysis of noninvasive imaging is a widely used approach to quantify intratumor heterogeneity [ 34 ]. Previous studies have shown that textural features can effectively predict treatment response and patient survival for various types of cancer [ 30 , 35 , 36 ]. Our results indicated that SUV kurtosis and LZHGE GLZLM might improve the risk stratification in HL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics analysis of noninvasive imaging is a widely used approach to quantify intratumor heterogeneity [ 34 ]. Previous studies have shown that textural features can effectively predict treatment response and patient survival for various types of cancer [ 30 , 35 , 36 ]. Our results indicated that SUV kurtosis and LZHGE GLZLM might improve the risk stratification in HL patients.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated 20 publications on breast cancer [59,[188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206], all of them using FDG as the radiotracer. The average number of patients was 118 (median = 81, range, 34-435).…”
Section: Breast Cancermentioning
confidence: 99%
“…In Moscoso et al [203], the authors showed that PET textural features are correlated with immunohistochemical factors and the immunohistochemical subtype of breast cancer using images acquired using a dedicated breast PET scanner. Finally, Lee et al [188] developed a statistical model combining clinicopathological factors and texture parameters from PET and CT images to predict individual responses to neoadjuvant chemotherapy.…”
Section: Breast Cancermentioning
confidence: 99%
“…Non-invasive image-derived biomarkers can also be generated from PET radiomics according to the intensity of the pixels, their associated parameters, and their positions (138). Based on the clinical application of PET-based techniques, several studies have focused on the clinical and technical feasibility of applying PET radiomics to diagnosis (139,140), staging (141)(142)(143), pathological characterization (17,18), NAC response (18,(144)(145)(146), and outcome prediction (147,148) in breast cancer. However, the difficulty in detecting the edges of breast lesions using CT limits the PET/CT in identifying the breast tumor and the alignment of the imaging modalities (141).…”
Section: Pet Radiomicsmentioning
confidence: 99%